Economic, financial and tax impact for implementation of IFRS (Resolution 414 of 2014) (2015)
The constant evolution of markets has generated economic, financial and tax regulations for structural changes in both the public sector and the private sector. The development of new financial possibilities for the different actors of the demand markets, accounting regulation, constantly updated its guidelines. Currently in Colombia , from issuing laws 1314 , 2009 , 2011 and 1450 , the convergence of the Colombian accounting regulations with international financial reporting standards becomes a priority in the management of regulators who do not measure impacts economic, financial and tax measures of their ......